2015
DOI: 10.1021/acs.jpca.5b09279
|View full text |Cite
|
Sign up to set email alerts
|

Promising Strategy To Improve Charge Separation in Organic Photovoltaics: Installing Permanent Dipoles in PCBM Analogues

Abstract: A multidisciplinary approach involving organic synthesis and theoretical chemistry is applied to investigate a promising strategy to improve charge separation in organic photovoltaics:installing permanent dipoles in fullerene derivatives. Firstly, a PCBM analogue with a permanent dipole in the side-chain (PCBDN) and its reference analogue without a permanent dipole (PCBBz) were successfully synthesised and characterised. Secondly, a multiscale modelling approach was applied to investigate if a PCBDN environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 47 publications
2
36
0
Order By: Relevance
“…In order to examine the fluorination effects of ANTh‐substituted polymer donors on their properties, the P1 – P3 were synthesized via Stille polymerization (Scheme S1, Supporting Information). [10b] The detailed procedures for the synthesis of polymers ( P1 – P3 and P(NDI2HD‐T2) ) are described in the Experimental Section (Supporting Information). Figure a represents the molecular structures of a series of polymer donors with different numbers of fluorine atoms (0, 1F, 2F) and poly[( N , N′ ‐bis(2‐hexyldecyl)napthalene‐1,4,5,8‐bis(dicarboximide)‐2,6‐diyl)‐alt‐5,5′‐(2,2′‐bithiophene)] ( P(NDI2HD‐T2) ) polymer acceptor used in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to examine the fluorination effects of ANTh‐substituted polymer donors on their properties, the P1 – P3 were synthesized via Stille polymerization (Scheme S1, Supporting Information). [10b] The detailed procedures for the synthesis of polymers ( P1 – P3 and P(NDI2HD‐T2) ) are described in the Experimental Section (Supporting Information). Figure a represents the molecular structures of a series of polymer donors with different numbers of fluorine atoms (0, 1F, 2F) and poly[( N , N′ ‐bis(2‐hexyldecyl)napthalene‐1,4,5,8‐bis(dicarboximide)‐2,6‐diyl)‐alt‐5,5′‐(2,2′‐bithiophene)] ( P(NDI2HD‐T2) ) polymer acceptor used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Also, Havenith and co‐workers showed that enhancing dipole moments in fullerenes can increase charge generation efficiency. [10a] Although there have been a few successful investigations on the correlation between Δ µ ge and photovoltaic parameters ( J SC and FF) in fullerene‐based PSCs, the influence of Δ µ ge of π‐conjugated polymers on charge generation of all‐PSCs has yet to be explored. This model study aims to provide an understanding of the impact of Δ µ ge of π‐conjugated polymers in order to overcome poor charge generation and enhance the PCE value of the all‐PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The Hummelen group recently also presented a promising strategy to improve charge separation by installing permanent dipoles in fullerene adducts (31 and 32; Figure 6). 55 Although no dielectric constants were measured for the synthesized fullerene derivatives, enhanced dipole moments were calculated when specific functional groups were introduced to increase the electronic polarization. Modeling showed that addition of a certain amount of derivative 31 to the active layer blend facilitated charge separation in the proximity of the central donor-acceptor complex.…”
Section: High-εr Acceptor Materialsmentioning
confidence: 99%
“…Using density functional theory calculations, Kraner et al have shown that adding polar groups could be an effective way to increase the dielectric constants of conjugated materials. Several groups have attempted to modify fullerenes to increase the dielectric constant by polar substituents, showing an increase in dielectric constants from 3.9 to ≈5 . While Donaghey et al reported nonfullerene acceptors with remarkably high dielectric constants up to 9.8 by adding oligo(ethylene oxide) chains to the backbones, no device performance was reported .…”
Section: Introductionmentioning
confidence: 99%